The feasibility of combined transcatheter arterial chemoembolization and radiotherapy for advanced hepatocellular carcinoma. (12th January 2014) - Cho, Ju‐Yeon; Paik, Yong‐Han; Park, Hee Chul; Yu, Jeong Il; Sohn, Won; Gwak, Geum‐Youn; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon; Yoo, Byung Chul
Abstract Background & Aims Sorafenib is regarded as the standard treatment of care in Barcelona Clinic Liver Cancer (BCLC) stage C patients. However, the modest overall survival (OS) and disease control rate warrants for a better treatment modality. This study aimed to investigate the feasibility of combined transarterial chemoembolization and radiotherapy (TACE+RT) in comparison with sorafenib for advanced hepatocellular carcinoma (HCC). Methods and Materials From 2007 to 2011, a total of 116 patients with locally advanced HCC were retrospectively enrolled. Sixty‐seven patients treated with TACE+RT were compared with 49 patients treated with sorafenib. Propensity score matching generated a matched cohort composed of 27 patients from each group. OS was the primary endpoint for the analysis. Results At baseline, the sorafenib group had a tendency for a tumour size ≥10 cm, presence of lymph node metastasis and main portal vein tumour thrombosis compared to the TACE+RT group. The OS in the TACE+RT group was significantly longer compared to the sorafenib group (14.1 months vs. 3.3 months, P < 0.001). In the propensity score‐matched cohort, baseline characteristics did not differ between the two groups. The TACE+RT group showed prolonged OS compared to the sorafenib group (6.7 months vs. 3.1 months, P < 0.001). Multivariate analysis revealed that TACE+RT was the only independent prognostic factor associated with survival in the propensity score‐matched cohort (HR = 0.172, P < 0.001). Conclusions The OS of TACE+RT was longer compared to sorafenib treatment in locally advanced HCC patients without distant metastasis. Further prospective studies are warranted to confirm these findings.